Characterizing Holocene sediments for assessing coastal-deltaic subsidence: the role of cone penetration tests and geomechanics - Buffardi, Carla; Minderhoud, Philip S. J.; Mandolini, Alessandro; Ruberti, Daniela (Frontiers in Earth Science, 2025)
River deltas and coastal-deltaic plains are, by nature, subjected to land subsidence from the consolidation of shallow, unconsolidated Holocene sediments. The spatio-temporal potential and occurrence of shallow coastal-deltaic subsidence—caused by both natural and anthropogenic factors—are highly dependent on geological and geotechnical Holocene stratigraphic characteristics. In this study, we utilized new CPT/CPTu measurements from the Volturno coastal deltaic plain (northern Campania, Italy) to geomechanically characterize the Holocene sedimentary facies, highlighting the great potential of this approach. The results reveal that although different facies associations may share similar lithologic compositions, their geotechnical behaviors may be strikingly dissimilar. These differences are attributable to varying paleo-depositional environments and sedimentary processes that create distinctive geomechanical fingerprints governing their consolidation behavior. These variable characteristics underlie, and in part explain, the spatial patterns in observed subsidence rates. The increased geomechanical insights advance our understanding of the spatio-temporal consolidation of the Holocene sedimentary sequence and its various depositional facies beyond standard lithological geotechnical characterization. In addition, they also enable further explorations, such as simulating 3D Holocene delta growth and evolutionary sediment compaction using numerical models.